Mengimplementasikan Pengetahuan Konten Pedagogis dalam Pendidikan Jasmani: Mengintegrasikan TGfU dan GPAI dalam Kerangka Tinjauan Sistematis - Alfina Wahyu Fernanda; Moh Alfi Mabruri; Dimas Candra Rahma Wiguna; Suroto (MAN Insan Cendekia Jambi, 2026)
The low quality of learning experiences in Physical Education, Sports, and Health (PE) is currently a crucial issue exacerbated by the dominance of traditional, mechanistic learning models. In fact, the implementation of the PE curriculum in Indonesia is heavily dominated by game-based activities, where the implementation rate of big ball games reaches 60% to 76%, far exceeding other sports materials. This article aims to analyze the development of Pedagogical Content Knowledge (PCK) studies in the context of Physical Education to map conceptual trends and identify implementation gaps in the literature. This study used the Systematic Literature Review (SLR) method with the PRISMA protocol on 24 articles indexed by Scopus between 2016 and 2025. The findings indicate that PCK develops through three main axes: mastery of specific content (SCK), embodiment in practice (enacted PCK), and technology integration (TPACK). However, the literature identifies obstacles in the form of low teacher SCK and research focuses that remain conceptually partial. In response, this article offers an integrative framework that connects PCK with the Teaching Games for Understanding (TGfU) model and the Game Performance Assessment Instrument (GPAI). The synergy of these three elements creates a learning design that aligns with the principle of constructive alignment, resulting in a more meaningful, structured, and accountable PE instructional process in measuring student performance.